Analysis of Semantic Relation in Short Story: Semantics Approach - Gilbert Adrian; Muhammad Ridho Fajar Nugraha; Gaguk Rudianto (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This research entitled Analysis of Semantic Relation in Short Story: Semantics Approach discussed the semantic relation used in the short stories by Kate Chopin. The objective of this study is to find and identify the kinds of semantic relation used in the short stories written by Kate Chopin and compare the semantic relation found in each short story. The research method for this research is qualitative descriptive. The data for this research will be the three of the short stories written by Kate Chopin: The Story of an Hour, Regret, and A Respectable Women. The method for this research will include collecting the words or phrases that have semantic relation and those words will be later categorized in their kind of semantic relation to compare the semantic relation used in Kate Chopin’s short stories.